Antibacterial Activity of Piliostigma thonningii Leaf Extract against Gram-Negative Bacteria Isolated from Urine Samples - Muhammad Muhammad, Shamsudeen; Saadu, Murtala; Musa, Isah; Aishat Motunrayo, Titilope (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2025)
The rise of antibiotic-resistant uropathogens has intensified the search for alternative antimicrobial agents, particularly from medicinal plants. Piliostigma thonningii, traditionally used to treat infections in African ethnomedicine, was investigated for its antibacterial efficacy against Gram-negative bacteria isolated from urine samples. Urine samples were collected and cultured on MacConkey agar. Pure isolates were subjected to Gram staining and a series of biochemical tests for identification following standard protocols. Crude leaf extracts of P. thonningii were prepared and subjected to phytochemical screening. Antibacterial activity was assessed using the agar well diffusion method at 100–400 mg/mL concentrations, with ciprofloxacin (10 µg) serving as a reference standard. Escherichia coli was the most prevalent isolate (51.43%), followed by Klebsiella pneumoniae (28.57%) and Enterobacter cloacae (20.00%). Phytochemical analysis revealed the presence of flavonoids, tannins, saponins, alkaloids, and terpenoids. The extract demonstrated dose-dependent antibacterial activity, with the highest inhibition against E. coli (23.0 ± 4.79 mm at 400 mg/mL). Although ciprofloxacin showed superior activity, the plant extract exhibited considerable zones of inhibition, particularly at higher concentrations. The study supports the traditional use of P. thonningii for treating bacterial infections and highlights its potential as a source of bioactive compounds. Further studies are needed to isolate active constituents, evaluate toxicity, and validate efficacy through in vivo models.